INVESTIGATION AND COMPARISON OF CHATGPT AND GOOGLE GEMINI EFFICIENCY IN EDUCATION, DESIGN AND ENGINEERING ANALYSIS - H. Ghashochi Bargh; M. H. Sadr; A. Aghababaee (آموزش مهندسی ایران)
In this paper, the potential use of ChatGPT and Google Gemini in engineering education, design, and analysis is investigated and compared through a multiple case study method and the results of other studies are also used in this purpose. For several different engineering cases, it is ilustrated how students and engineers can use them. The capabilities, limitations, advantages and disadvantages of using these chatbots in engineering research and education are also discussed, and practical strategies for the effective use of the two chatbots by engineering students, professors, and designers are presented. The results show that the use of sufficient and clear input information in the above chatbots plays a decisive role in reaching the appropriate response. Also, the two chatbots are not very successful in the face of complex engineering problems and in some cases, they refer the problems to expert consultation or to use other engineering softwares. On the other hand, for simple computational engineering problems, ChatGPT usually does not give correct answers, unlike Google Gemini. Overall, the mentioned chatbots can significantly facilitate the work of engineers in design, calculations, material selection, and other tasks, and also, provide significant assistance in the field of education.